The Psychological Impact of the Tertiary Hospital Reappraisal on Resident Doctors in the Post-pandemic Era: A Cross-sectional Study in Ningbo - Shao, Zhonghao; Cao, Angyang; Luo, Wenjun; Zhou, Yanling; Wang, Jianhua; Gui, Yu; Gao, Bin; Xu, Zhipeng; Zhu, Binbin; Sheng, Zhiren (Frontiers in Psychiatry, 2022)
Abstract Objective: Resident doctors with mental disorder are vulnerable and maybe the candidate of medical negligence, which is detrimental for the patient’s safety and shed shame on the doctor’s career. The study aimed to assess the psychosocial impacts of the hospital reappraisal during the post-pandemic era of COVID-19 and analyze potential risk factors influencing their mental health. Method: A total of 96 resident doctors from the affiliated hospital of the medical school of Ningbo University were invited to complete the questionnaires. The resident doctors’ mental health was assessed by an online survey. Results： According to our study, the prevalence of symptoms of anxiety and depression in the resident doctors in our institution was 61.5% and 59.4%, respectively. The trainees who were worried about clinical skills tend to have anxiety symptoms under online education ( OR=3.436,95%CI：1.122-10.526). Compared with participants who were assigned by other hospitals, social trainees (OR: 7.579, 95%CI: 1.747-32.885) and full-time masters (OR: 5.448, 95% CI: 1.586-18.722) were more likely to have anxiety symptoms. Participants without a labor contract (OR=3.257, 95% CI: 1.052-10.101) had a high risk of depression symptoms. Participants who spent more time learning the details prepared for the tertiary hospital reappraisal were significantly more likely to develop anxiety and depressive symptoms. Conclusion: This study suggested that the tertiary hospital reappraisal program has an impact on the high incidence of anxiety and depression of the young resident doctors during the post-pandemic era of the COVID-19 in Ningbo. Psychosocial interventions for the resident doctors are urgently needed to support them to overcome mental problems. Keywords: Post-pandemic; the tertiary hospital reappraisal; resident doctor; mental health; psychological problem.